Lipoprotein(a) and its linear association with all-cause and cardiovascular mortality in patients with acute coronary syndrome - Qin, Ke; Zhang, Tingyuan (Frontiers in Endocrinology, 2025)
ObjectiveThis study aimed to investigate the linear association between lipoprotein(a) [Lp(a)] levels and all-cause and cardiovascular mortality in patients with acute coronary syndrome (ACS).MethodsThis retrospective cohort study included 578 patients with ACS who were hospitalized at Henan Provincial People’s Hospital between January 2020 and January 2024. Patients were categorized into two groups: lower Lp(a) group (≤ 300 mg/L) and higher Lp(a) group (> 300 mg/L). Kaplan-Meier survival analysis, Cox regression models, subgroup and sensitivity analyses were used to evaluate the association between Lp(a) and all-cause and cardiovascular mortality. Restricted cubic spline (RCS) analysis was conducted to explore nonlinear associations.ResultsDuring a median follow-up of 27.5 months, a total of 124 all-cause deaths occurred (21.5%), of which 79 cases (13.7%) were classified as cardiovascular deaths. Compared to the lower Lp(a) group, the higher Lp(a) group exhibited a significantly increased risk of all-cause and cardiovascular mortality across all models. In the fully adjusted model (Model 3), the hazard ratio (HR) for all-cause mortality was 1.719 (95% confidence interval [CI]: 1.197–2.470, P = 0.003), while the HR for cardiovascular mortality was 2.505 (95% CI: 1.529-4.102, P < 0.001). In an additional analysis using a 500 mg/L cut-off, patients with Lp(a) > 500 mg/L had a significantly higher risk of cardiovascular mortality (HR = 2.209, P = 0.001), while the association with all-cause mortality (P = 0.284) was not statistically significant in the fully adjusted model. When Lp(a) was analyzed as a continuous variable, each 90 mg/L increase in Lp(a) was associated with a 5% higher risk of all-cause mortality (HR = 1.052, 95% CI: 1.003-1.104, P = 0.038), and each 45 mg/L increase was associated with a 5% higher risk of cardiovascular mortality (HR = 1.054, 95% CI: 1.026-1.084, P < 0.001). For log10-transformed Lp(a), the HR was 1.954 (95% CI: 1.252-3.050, P = 0.003) for all-cause mortality and 3.913 (95% CI: 2.108-7.265, P < 0.001) for cardiovascular mortality. Similarly, for standardized Lp(a) (Z-score), the HR was 1.178 (95% CI: 1.009-1.375, P = 0.038) for all-cause mortality and 1.408 (95% CI: 1.179-1.681, P < 0.001) for cardiovascular mortality. Most subgroup analyses showed that elevated Lp(a) levels were significantly associated with an increased risk of all-cause and cardiovascular mortality (P < 0.05). Sensitivity analyses confirmed the robustness of the findings, with significant associations persisting after excluding patients with early mortality or without stent implantation. Kaplan-Meier analysis showed that both all-cause and cardiovascular survival rates were significantly lower in the high Lp(a) group compared to the low Lp(a) group (P < 0.001 for both). RCS analyses revealed a linear positive association between Lp(a) levels and both all-cause and cardiovascular mortality.ConclusionsHigher Lp(a) levels were independently and linearly associated with an increased risk of all-cause and cardiovascular mortality in ACS patients.